Geo-Architecture and Landscape in China’s Geographic and Historic Context Volume 1 Geo-Architecture Wandering in the Landscape - Wang, Fang (Springer Nature Singapore : Imprint: Springer, 2016)
XXXI, 297 p. 338 illus., 260 illus. in color.